SISTEM PAKAR PENDIAGNOSA KERUSAKAN PADA KAMERA DIGITAL - Akik Hidayat; Yusuf Sumaryana (JUTEKIN (Jurnal Teknik Informatika), 2015)
Damage components of digital cameras is a case that requires the help of a specialist (technician). In solving the problem, experts rely on its knowledge, obstacles often experienced when relying on the services of an expert are the costs relatively little and is also an expert will not always be available to serve the client at all times.        The main discussion in this study is to design and manufacture of an expert system to. The development of this expert system uses forward chaining inference method, which is a process of inference that initiates a search of symptoms or data to the conclusion.          Expert systems are systems that try to adopt human knowledge to computer, so that the computer can solve such problems is usually done by experts.          The purpose of this software is to create an expert system that is used to diagnose damage to the hardware on a laptop that can do early prevention. Making this expert system using Microsoft Visual Basic 6.0 with Microsoft Access 2003 databaseKeyword : expert System, Camera Digital, Visual basic 6.0